MENINGKATKAN KEMAMPUAN BERBICARA ANAK MELALUI BERMAIN RODA GAMBAR - Wulandari, Addiniah Sukmawati (JIV-Jurnal Ilmiah Visi, 2013)
The purpose of this research is to improve speaking skills of children aged 6-7 years by playing a picture wheel in SDN Rawamangun 15 Pagi, Jakarta Timur. This research using action research method that was done by two cycle consisting of planning, acting, observing, and reflecting. The research subject are children aged 6-7 years who had problem in the ability of speaking as many as 8 childrens. The analysis of data was obtained from the comparison between the ability of childrens speaking before and after implemetation of the action. The final result from the overall analysis of data percentage reach to 78,3%. Based on the percentage of end the cycle of this research, so it was stated that the hypothesis can be accepted. Then it can be concluded that playing a picture wheel can improved children speaking ability of aged 6-7 years. The implication of this research is playing a picture wheel can be alternative for improving children speaking ability of aged 6-7 years. The reach of children speaking ability can showed by word producing, conveying the idea, asking the question, expressing emotion, and conveying the information.